FEATURE OF CELLULAR COMPOSITION OF THE GUMS IN GENERALIZED PERIODONTITIS - Gasyuk, N.V.; Yeroshenko, G.A. (World of Medicine and Biology, 2014)
An article presents the results of a research of the cellular composition of epithelial and connective tissue fractions of periodontal pockets in patients with chronic generalized periodontitis. It was established that due to prolonged presence of inflammation in the periodontium, a violation of epithelial keratinization occurs, that is characterized by the absence of all epithelial cells and the change in percentage of cell avanguard. Three types of smears were determined, according to a number of hematogenous cells prevalence, that is in comparison with a history of patients, regarding the frequency of exacerbations, made it possible to formulate criteria for prognostic clinical course of generalized periodontitis. The above mentioned, makes it possible to assert that cellular and humoral immunity of periodontal pockets are closely related together, primarily by polymorphonuclear leukocytes and macrophages. These cells play a key role in the inflammatory response and protecting the body from external influence factors including bacteria and their toxins.
Keywords: periodon; epitheliocytes; generalized periodontitis; leukocytes